Analisa Gangguan Teknis Pada Kwh Meter Prabayar 1 Phasa Guna Menjaga Kualitas Pelayanan Pelanggan di PT PLN (PERSERO) ULP Jayapura - Seno, Titus Tandi; Putri, Ni Made Feby Anggraini; Patoding, Hestikah Eirene (Neolectura, 2024)
PT PLN (Persero) is a company engaged in the electricity sector with the function of serving all communities throughout Indonesia, trying to make efforts to improve the best service quality to satisfy customer needs. The form of electricity service to the community currently has 2, namely postpaid electricity services and prepaid electricity services. To find out whether the service has been provided to the community optimally, it is necessary to analyze the cause of damage to the 1 Phase Prepaid kWh Meter. Disturbances are often found in the Prepaid kWh Meter (MPB) because the prepaid kWh meter tends to be more sensitive and easily damaged. This study was conducted to determine the cause of damage to the 1 Phase Prepaid kWh Meter with the location of PT PLN (Persero) ULP Jayapura. The method used is a quantitative approach to process data obtained from the location, which is data in the form of numbers. The results obtained showed that the highest number of complaints of disturbances occurred in 2022 with 3283 disturbances, in 2023 with 1962 disturbances, and in 2021 with 1341 disturbances. The kWh meter brands that are often damaged are Hexing 2117 units from a total of 6586 complaints, followed by the Sanxing brand with 2083 units, the Actaris brand with 760 units, the Metbelosa brand with 756 units, the Meisys brand with 358 units, the Itron brand with 349 units, and finally the Fuji brand with 163 units. The solution to overcome the damage is to replace the damaged kWh.